PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN KONSEP DIRI FISIK SISWA KELAS X MIA SMA NEGERI 2 PEKANBARU - Sesi Pujiasti; Raja Arlizon; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is aimed to find out the effect of group counseling servicetoward students’ physical self-concept at the experiment group. The methodology of thisresearch is real-experimental method with control group experiment. The sample of thisresearch was 20 students of X MIA Senior High School 2 Pekanbaru. The result of thisresearch is to find out the difference between post test at the experiment group and posttest at the control group, the researcher used SPSS program with Mann Whitneyformula and got the result Z = -2.734 with sig. (2-tailed) is 0.006. Because of the valueof sig. (2-tailed) 0.006 < 0.05, therefore, it can be concluded that “there is a significantdifference between post test of students’ physical self-concept at the experiment groupand post test of students’ physical self-concept at the control group” and for thecontribution of group counseling service toward students’ physical self-concept is13.6%.Keywords: Group Counseling Service, Physical Self-Concept